Microtubule-associated protein 1A is a modifier of tubby hearing (moth1) - Ikeda, Akihiro (2002)
Once a mutation in the gene tub was identified as the cause of obesity, retinal degeneration and hearing loss in tubby mice1–2, it became increasingly evident that the members of the tub gene family (tulps) influence maintenance and function of the neuronal cell lineage3–6. Suggested molecular functions of tubby-like proteins include roles in vesicular trafficking4,7, mediation of insulin signaling8 and gene transcription9,10. The mechanisms through which tub functions in neurons, however, have yet to be elucidated. Here we report the positional cloning of an auditory quantitative trait locus (QTL), the modifier of tubby hearing 1 gene (moth1)11, whose wildtype alleles from strains AKR/J, CAST/Ei and 129P2/OlaHsd protect tubby mice from hearing loss. Through a transgenic rescue experiment, we verified that sequence polymorphisms in the neuron-specific microtubule-associated protein 1a gene (Mtap1a) observed in the susceptible strain C57BL/6J (B6) are crucial for the hearing-loss phenotype. We also show that these polymorphisms change the binding efficiency of MTAP1A to postsynaptic density molecule 95 (PSD95), a core component in the cytoarchitecture of synapses. This indicates that at least some of the observed polymorphisms are functionally important and that the hearing loss in C57BL/6J-tub/tub (B6-tub/tub) mice may be caused by impaired protein interactions involving MTAP1A. We therefore propose that tub may be associated with synaptic function in neuronal cells.